Curcumin Suppresses the Colon Cancer Proliferation by Inhibiting Wnt/β-Catenin Pathways via miR-130a - Dou, Huiqiang; Shen, Renhui; Tao, Jianxin; Huang, Longchang; Shi, Haoze; Chen, Hang; Wang, Yixin; Wang, Tong (Frontiers in Pharmacology, 2017)
Curcumin exhibits anti-tumor effects in several cancers, including colorectal carcinoma (CRC), but the detailed mechanisms are still unclear. Here we studied the mechanisms underlying the anti-tumor effect of curcumin in colon cancer cells. SW480 cells were injected into mice to establish the xenograft tumor model, followed by evaluation of survival rate with the treatment of curcumin. The expression levels of β-catenin, Axin and TCF4 were measured in the SW480 cells in the absence or presence of curcumin. Moreover, miRNAs related to the curcumin treatment were also detected in vitro. Curcumin could suppress the growth of colon cancer cells in the mouse model. This anti-tumor activity of curcumin was exerted by inhibiting cell proliferation rather than promoting cell apoptosis. Further study suggested that curcumin inhibited cell proliferation by suppressing the Wnt/β-catenin pathway. MiR-130a was down-regulated by curcumin treatment, and overexpressing miR-130a could abolish the anti-tumor activity of curcumin. Our study confirms that curcumin is able to inhibit colon cancer by suppressing the Wnt/β-catenin pathways via miR-130a. MiR-130a may serve as a new target of curcumin for CRC treatment.